Reductive Alkylation of Candida Rugosa Lipase: Structural Approaches - Tejo, Bimo Ario (2004)
The properties of alkylated lipase are successfully explored through experimental and molecular modelling methods. Alkylation was done using aldehydes with different degree of modification to represent different levels of hydrophobicity which is important for enzymes to work in nonaqueous environment. Far ultraviolet circular dichroism (CD) spectroscopy of the lipase in aqueous solvent shows that increasing the degree of modification from 49% to 86% resulted in loss in secondary structure which is attributed to the enzyme unfolding. The secondary structure elements of the CD spectra of native and modified lipase were analysed using the CDPro software and the K2D program. Both methods yield the same results in that the ratio of α-helical structure is lost. This result explains why alkylated lipases have much lower activity in an aqueous environment. Molecular modelling simulations were performed to study the structural and dynamical changes of the lipase upon different levels of modification. Simulations were run for 1 ns (300 K) with five different initial velocities to obtain better conformational sampling. Two solvent systems were used: TIP3P water model and carbon tetrachloride (CCl4) solvent model in periodic boundary condition (PBC). Generally, lipases simulated in water are less deviated in term of root mean square deviations (rmsd) compared to lipases simulated in CCl4. Lid movements are essential for lipase function, both in water and waterlipid environments. Analyses of lid dynamics were done using timecorrelation function and second-order Legendre polynomial function. Lipase in water and CCl4 shows different properties of dynamics. Without alkylation, the time correlation function of lipase in water shows one slow exponential decay with a correlation time of τ = 92.8 ps. In contrast, for simulations in CCl4 the lid has a more complex dynamics. Exponential fit of open CRL in CCl4 results in two different τ values: a fast motion τ1 = 5.6 ps and a slow motion τ2 = 163.8 ps.Upon alkylation, different levels of modification show different properties of lid motions. In CCl4, lid region is highly stabilised upon 95% alkylation with slow motion mode of τ1 = 4.1 ps and τ2 = 577.8 ps. Slow motion effect of lid region is also observed at 63% with τ1 = 2.9 ps and τ2 = 209.2 ps and 43% modification with τ1 = 3.4 ps and τ2 = 117.9 ps. In water, 43% and 95% modification show similar motion with unmodified lipase, with one slow exponential decay of τ = 142.8 ps and 133.6 ps, respectively. However, 63% modification shows more complex dynamics with different τ values which mimics the dynamics properties in CCl4. A novel lid-locking mechanism which stabilises the opening form of lid region has been observed during simulations of unmodified CRL in CCl4, i.e. a salt bridge between Lys85 and Asp284. This salt bridge is highly stabilised on unmodified lipase with a distance of 3.3 Å compared with lipase simulated in water with a distance of 15.25 Å. Alkylation at 43% causes the salt bridge to be deformed in CCl4 with a distance of 6.03 Å; however, 63% modification stabilises the salt bridge with a distance of 3.88 and 95% modification shows the most stabilising effect with a distance of 3.19 Å.